2018
DOI: 10.1051/0004-6361/201732471
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and wave-like properties of the average solar supergranule

Abstract: Context. Solar supergranulation presents us with many mysteries. For example, previous studies in spectral space found that supergranulation has wave-like properties. Aims. Here we study, in real space, the wave-like evolution of the average supergranule over a range of spatial scales (from 10 to 80 Mm). We complement this by characterizing the evolution of the associated network magnetic field. Methods. We use one year of data from the Helioseismic and Magnetic Imager (HMI) onboard the Solar Dynamics Observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…North-South alignments of supergranules have also been found in the polar regions by Nagashima et al (2011) using local helioseismology with Hinode/SOT data. A recent study by Langfellner et al (2018) using both time-distance helioseismology on SDO/HMI data and correlation tracking appears to further confirm the results of on the wave-like oscillatory properties of the dynamics in the range of scales 50 < < 120 comparable to or slightly larger than the supergranulation scale.…”
Section: Effects Of Rotationsupporting
confidence: 66%
“…North-South alignments of supergranules have also been found in the polar regions by Nagashima et al (2011) using local helioseismology with Hinode/SOT data. A recent study by Langfellner et al (2018) using both time-distance helioseismology on SDO/HMI data and correlation tracking appears to further confirm the results of on the wave-like oscillatory properties of the dynamics in the range of scales 50 < < 120 comparable to or slightly larger than the supergranulation scale.…”
Section: Effects Of Rotationsupporting
confidence: 66%
“…For example, it may be possible to produce models in which the emergence locations are in some way related to supergranulation-scale diverging flows rather than converging flows. The connection between the locations of supergranulation centers and supergranulation-scale convergence regions is only statistical in nature ( Langfellner et al 2018 ), so that there is a distinction between models based on convergence centers and supergranule centers. We also note that the model presented here is the simplest model that we found that provides a qualitative match to the observations.…”
Section: Discussionmentioning
confidence: 99%
“…We use maps of the horizontal near-surface divergence that were obtained by Langfellner et al (2018) using Dopplergrams and intensity images from HMI/SDO. The data cover 365 days from May 2010 through April 2011.…”
Section: Divergence Maps Of Supergranular Flowsmentioning
confidence: 99%
“…Using the intensity images and LCT of granules (November & Simon 1988), Langfellner et al (2018) obtained estimates of the two horizontal flow components for the same spatial and temporal coverage. This results in maps with 97×97 pixels, each of size (5 × 0.348 Mm) 2 .…”
Section: Divergence Maps Of Supergranular Flowsmentioning
confidence: 99%
See 1 more Smart Citation